Retrospective study of salivary gland diseases in dogs and cats presented to the University Veterinary Hospital Universiti Putra Malaysia - Tan, Aarin Li Shuen
Salivary gland diseases are uncommonly reported in dogs and cats. There is also limited research conducted at the University Veterinary Hospital (UVH) and Universiti Putra Malaysia (UPM) on salivary gland diseases in dogs and cats. This retrospective study aimed to analyse the clinical presentation, treatment and outcome of salivary gland diseases in dogs and cats presented to the University Veterinary Hospital, Universiti Putra Malaysia. Case logbooks and medical records of the University Veterinary Hospital, Universiti Putra Malaysia, were retrospectively searched to identify dogs and cats diagnosed with salivary gland diseases between January 2013 and August 2023. A total of 12 patients with salivary gland diseases, consisting of seven cats and five dogs, were identified in this retrospective study. The diagnoses included cervical sialocele (7/12 cases), sublingual sialocele or ranula (5/12 cases), salivary gland prolapse (1/12 cases), and salivary gland neoplasia (1/12 cases). The mean age of affected dogs and cats was 7.4 y and 4.6 y, respectively. The most common clinical signs for dogs were mandibular or submandibular swelling, neck swelling, and loud snoring while sleeping. Cats' most common clinical signs were sublingual swelling, mandibular or submandibular swelling, halitosis and hypersalivation. Treatment comprises conservative treatment and surgical approaches to manage salivary gland diseases. Conservative treatment involves only prescription medications and close monitoring of the clinical signs without invasive treatment such as surgery. Four dogs and two cats were treated conservatively before proceeding with the surgical approach; the mean duration of conservative treatment was 102.8 days and 19 days, respectively. Recurrence after surgery was identified in two of five dog cases and one of seven cat cases. Both recurrence cases in dogs were initially treated with unilateral excision of affected salivary glands, while the recurrence in cats was initially treated with marsupialization. In conclusion, salivary gland diseases in dogs and cats are relatively rare. No patient has achieved complete recovery through conservative treatment, suggesting a better prognosis can be achieved with an appropriate surgical approach compared to conservative treatment.